The evaluation of sources of knowledge underlying different conceptual categories - Gainotti, Guido; Spinelli, Pietro; Scaricamazza, Eugenia; Marra, Camillo (Frontiers in Human Neuroscience, 2013)
According to the “embodied cognition” theory and to the “sensory-motor model of semantic knowledge”: (a) concepts are represented in the brain in the same format in which they have been constructed by the sensory-motor system and (b) various conceptual categories differ for the weight that different kinds of information play in their representation. In our study, we have tried to check the second assumption by asking normal elderly subjects to rate their subjective evaluation of the role that various perceptual, motor and language-mediated sources of knowledge could have in the construction of different semantic categories. Our first aim consisted in rating the influence that different sources of knowledge could have in the representation of animals, plant life and artifact categories, rather than in those of living and non-living beings, as many previous studies on this subject have made. We also tried to check the influence of age and stimulus modality on these evaluations of the ‘sources of knowledge’ underlying different conceptual categories. The influence of age was checked by comparing results obtained on our group of elderly subjects with those obtained in a previous study, conducted with the same methodology on a sample of young students, whereas the influence of stimulus modality was assessed by presenting the stimuli in the verbal modality to 50 subjects and in the pictorial modality to 50 other subjects. The distinction between ‘animals’ and ‘plant life’ within the ‘living’ categories was confirmed by the analysis of their prevalent sources of knowledge and by a cluster analysis, which allowed to distinguish fruits and vegetables from animals. Furthermore, results of the study showed: (a) that the visual modality was considered by our subjects as the main source of knowledge for all the categories taken into account; (b) that in biological categories the next more important source of information was represented by other perceptual modalities, whereas